084 Short-Term Stretched Penile Length Analysis for Subsequent Erectile Dysfunction after Robotic-Assisted Radical Prostatectomy with Bilateral Neurovascular Bundle Preservation. (1st May 2022) - Yang, CH; Lin, YS; Ou, YC; Weng, WC; Huang, LH; Lu, CH; Hsu, CY; Tung, MC
ABSTRACT: Introduction: Stretched Penile Length (SPL) is observed to shrink after radical prostatectomy (RP) and has chances resuming the length as long as 12 months. Objective: To assess the short-term SPL change from patients after robotic-assisted radical prostatectomy (RARP) with bilateral neurovascular bundle (NVB) preservation and experiencing subsequent erectile dysfunction (ED). Effects from tadalafil, post-operative androgen deprivation therapy (ADT), and no medication or intervention are compared. Methods: From April to December 2018, patients developing ED (IIEF-5<22) after RARP with bilateral NVB preservation were included. SPL was measured as length from pubic symphysis to external urethral opening. Tadalafil 5 mg once daily (Group 1), postoperative ADT (Group 2) and control group (Group 3) were classified. Postoperative ADT was prescribed during the whole periods of 6 months for surgical adverse effects in group 2. Follow-ups were arranged 2 weeks after operation in the first time, and then every month up to 6 months. Student t test, chi-square test and SAS 9.4 were utilized to see if significant difference when p<0.05. Results: With 64 men, 1 was excluded for preoperative ADT use. SPL-related comparisons were listed at Table 1. Preoperative SPL was measured without differences. Generally, in 6-month span, more men were with increased SPL in group 1 than in group 3, and also more with deterioration compared to group 3 (p=0.048). Same trend was observed in group 2 compared to group 3 (p=0.036). Men in group 1 (at the time deciding to take tadalafil) experienced a worse shortening SPL than group 3 (the 30–day change after operation) (p< 0.0001). Significantly improvement on SPL between before (7.93±1.89 (median: 7.5) cm) and after (8.59±2.17 (median:9) cm) tadalafil in group 1 (p=0.037) and also significantly improved against the SPL change from post-operative 30-day to 5-month of group 3 (p=0.004). Conclusions: In our analysis, 63.7% of subsequent ED after RARP with bilateral NVB preservation would experience SPL shortening around 3 cm (around 30% of preoperative SPL) if only observation in 6 months after operation. Postoperative ADT for 6 months would contribute to approximately additional 15% shortening rates with the same degree. Significant improvement around 1 cm (around 10% of the preoperative SPL) on SPL was observed after tadalafil 5 mg once daily with median 4-month prescription. Disclosure: Work supported by industry: no.